Growth performance of jute (Corchorus capsularies L.) as influenced by different organic manures - Qulsum, U; Meem, FF; Promi, RS; Zaman, JR; Ara, MF; Rahman, MK (Journal of Biodiversity Conservation and Bioresource Management, 2021)
A pot experiment was carried out in 2019 in the net house of the Department of Soil, Water and Environment, University of Dhaka, to evaluate the growth and yield of Jute plants (Corchorus capsularies L.) by applying different types of organic manures. Eight different types of organic manures viz. ACI, BGF-1, Mazim, Vermicompost, Shufola, GTS, Green and Poultry manures were collected from the local market. The experiment was set up following a completely randomized design (CRD) with nine treatments and three replications consisting of twenty-seven pots. Significant variation was observed in different growth and yield contributing characters. The highest plant height (19.83cm) in poultry manure, leaf number (8.33/plant) was observed in Green manure, leaf area (21.93 cm2 / plant) in Poultry manure, fresh weight (3.18g) and dry weight (2.25 g) were found in Poultry manure, stem girth (1.67 cm/plant) in Vermicompost, branch number (8.6/plant) in Green manure. The highest nutrient uptake by plants (kg/ha) occurred in Poultry manure. The overall best growth was observed in Poultry manure. J. Biodivers. Conserv. Bioresour. Manag. 2020, 6(1): 17-24